Research and development of a vehicle simulation platform - Design of a flexible and versatile architecture for vehicle simulation to satisfy the needs of diagnostic applications - Axerot, Tomas (My University, 2011)
As the complexity of modern vehicles has grown, there have been higher demands on the diagnostic applications to support them. The applications used today to diagnose modern vehicles have a difficult task. They need to keep up with rapid changes, complex systems, and variant management. This makes it challenging to develop and test them in an efficient way. These problems can be solved or mitigated with a simulator which the diagnostic application can be run against. This thesis will investigate what challenges today's diagnostic applications are facing and how a flexible and versatile vehicle simulation can be designed. To create the perfect simulation, you would probably spend as much time as it takes implementing the system you are supposed to simulate. The most important decisions when creating the simulator are: which level of detail to simulate, which level of flexibility to customize the simulation, and how the simulation itself will be described. Two common vehicle description formats have been looked into: ODX and ASAP2. ODX contains many components that offer great flexibility such as its parameter, memory, and service structures. The simulator prototype developed in this project uses many ideas from ODX and ASAP2 to build its simulation logic. Allt eftersom komplexiteten i moderna fordon har ökat ställs det högre krav på diagnostiska applikationer för att stödja dem. De program som används idag för att diagnostisera moderna fordon har en svår uppgift. De måste hålla jämna steg med snabba förändringar, komplexa system och varianthantering. Detta gör det utmanande att utveckla och testa dem på ett effektivt sätt. Dessa problem kan lösas eller mildras med en simulator som den diagnostiska applikationen kan köras mot. Detta examensarbete kommer att undersöka vilka utmaningar dagens diagnostiska applikationer står inför och hur en flexibel och mångsidig fordonssimulering kan utformas. För att skapa den perfekta simuleringen skulle du antagligen spendera lika mycket tid som det tar att utveckla systemet du ska simulera. De viktigaste besluten när du skapar simulatorn är: vilken nivå av noggrannhet ska simuleras, graden av flexibilitet för att anpassa simuleringen och hur simuleringen kommer att beskrivas. Två vanliga fordonsbeskrivningsformat har undersökts: ODX och ASAP2. ODX innehåller många komponenter som ger stor flexibilitet såsom dess parameter, minne och servicestrukturer. Simulatorprototypen som har utvecklats i detta projekt använder många idéer från ODX och ASAP2 för att bygga sin simuleringslogik.
Keywords: Datorteknik; Computer Engineering